(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Diuretics are widely employed drugs used to treat extra cellular fluid volume expansion caused due to renal, cardiac, liver disorders etc. These diuretics are effective but have side effects. Acalypha Indica Linn is a herb of Euphorbiaceae family, found throughout India as a weed. Many studies have been carried out but sufficient data is not available to establish its diuretic activity. Hence the study is focused on the assessment of Harita Manjari for its diuretic action in animal model. Methods: The trial drugs are administered for 7 days prior to the day of evaluation of diuretic action; the rats were individually placed in the metabolic cages to collect urine. The volume of the urine collected in graduated vials was measured after 6 hours and expressed in terms of ml/100gm of body weight. Results: The invivo study demonstrated that crude suspension of Harita Manjari in a dose of 450mg/kg has significant diuretic activity. The statistical analysis has been carried out and results on continuous measurements are presented on Mean ± SEM were calculated. Urine output, pH and urine electrolytes were compared with control groups by one-way ANOVA followed by Dunnett’s multiple comparison test. The P Value <0.05 were considered as statistically significant. Conclusion: Order of diuresis: Crude suspension >Alcoholic extract >Aqueous extract.